Development of a Learning Management System Using Moodle in the Arabic Language Education Study Program / Pengembangan Learning Management System menggunakan Moodle pada Program Studi Pendidikan Bahasa Arab - Muhammad Zaky Sya'bani; Khairil Anwar (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
This research is motivated by the demands of the times in the world of education which require managers of educational institutions and stakeholders to be able to improve digital literacy skills. The Covid 19 pandemic situation makes learning to switch to learning in a structured network. This study aims to develop the Moodle Learning Management System in PBA Study Program and see the effectiveness of using the Moodle LMS. This research uses the R&D research method with the Borg and Gall development model. The results of this study are (1) The development of the Moodle LMS in this study uses the Borg and Gall development model. The courses that the researchers developed were fahmul masmu in PBA study programs. In the validity process of the Moodle LMS that was developed, the researcher presented 3 experts, namely: media, material and language experts. As for the results of the validity questionnaire, it was analyzed with Aiken validity which obtained a value of 0.88 with valid information for material, 0.89 with valid information for media and a value of 0.88 with valid information for language. (2) The effectiveness of using LMS Moodle in learning Arabic reaches 82.64% with the statement